2021
DOI: 10.7150/ijms.49126
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a three-microRNA signature as prognostic biomarker in patients with hepatocellular carcinoma

et al.

Abstract: Hepatocellular carcinoma (HCC), a common type of primary liver cancer, is one of the most aggressive malignant tumors worldwide. Although overall survival (OS) rates for HCC has significantly improved in recent years, however, the exact predictive value of microRNA (miRNA) for the prognosis of HCC has not yet been recognized. Here, we aimed to identify potential prognostic miRNAs involved in HCC by bioinformatics analysis and validated expression levels through quantitative polymerase chain reaction (qPCR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…The purpose of this study was to determine the value of clinical information about proteins carried by extracellular vesicles in HCC based on big data and bioinformatics methods. Bioinformatics research using big data has identified several biomarkers, such as Zhang et al finding that a three-miRNA signature can serve as an independent prognostic indicator for HCC patients [ 35 ], and Du et al revealing that a specific seven-biomarker signature may be clinically useful in predicting HCC prognoses in addition to conventional clinicopathological factors [ 36 ]. While the bioinformatics analysis methods for big data are generally the same, the research perspectives vary.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of this study was to determine the value of clinical information about proteins carried by extracellular vesicles in HCC based on big data and bioinformatics methods. Bioinformatics research using big data has identified several biomarkers, such as Zhang et al finding that a three-miRNA signature can serve as an independent prognostic indicator for HCC patients [ 35 ], and Du et al revealing that a specific seven-biomarker signature may be clinically useful in predicting HCC prognoses in addition to conventional clinicopathological factors [ 36 ]. While the bioinformatics analysis methods for big data are generally the same, the research perspectives vary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, mRNA, miRNA and circRNA were known as the RNA interaction molecules, which have important biological significance. 26 Previous research has reported that the ceRNA was associated with the molecular mechanism of cancers, such as breast cancer, 27 glioblastoma, 28 and lung cancer. 29 Our study performed an integrated analysis of circRNA-associated ceRNAs in >5 OS cell lines.…”
Section: Discussionmentioning
confidence: 99%
“… 31 Research has found that hsa-miR-760 is upregulated in hepatocellular carcinoma, and it could serve as a potential prognostic miRNAs of hepatocellular carcinoma. 26 However, it has been proved that hsa-miR-760 is downregulated in non-small cell lung cancer, and its expression suppresses the proliferation and metastasis of cells and enhances sensitivity to TNF-related apoptosis-inducing ligand. 32 , 33 These results suggested heterogeneity in tumor pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, compared with normal patients, the levels of miRNA-139-3p in the serum of HCC patients decreased, while those of miRNA-7-5p and miRNA-760 increased. Combined with ROC curve analysis, it was indicated that these three miRNAs were also of great diagnostic value for HCC [ 66 ]. Liver transplantation is an effective approach for the treatment of HCC, but there is always a risk of recurrence.…”
Section: Mirnas and Cancer Diagnosis And Prognosismentioning
confidence: 99%